HOW FEMALE UNIVERSITY STUDENTS IN KAZAKHSTAN EXPRESS THEIR FEMINIST IDENTITY IN DIFFERENT SOCIAL CONTEXTS: A QUALITATIVE STUDY BASED ON STUDENTS AT NAZARBAYEV UNIVERSITY - Armsan, Rebekka (School of Sciences and Humanities, 2023)
This research project examines the experiences which young women who study at Nazarbayev University (NU) and identify themselves as feminists encountered in different social contexts in Kazakhstan (unfamiliar/familial/university contexts), what they link their experiences to and what specific situations they have been in because of their feminist identity expression. Comparison of the experiences of female university students in familiar and new and unfamiliar social contexts provides insights into the ways in which feminist identity is negotiated and adapted in different settings, how and under which circumstances feminist identity of Kazakhstani women is revealed and concealed. To understand more about feminist identities in various social contexts the Identity Salience Theory will be applied to explain some of the processes related to revealing/concealing feminist identity.
Keywords: Type of access: Open Access; Female University Students; Feminist Identity; Kazakhstan; Nazarbayev University; feminism; feminists; identity salience theory